Effects of Intensive Systolic Blood Pressure Lowering on Cardiovascular Events and Mortality in Patients With Type 2 Diabetes Mellitus on Standard Glycemic Control and in Those Without Diabetes Mellitus: Reconciling Results From ACCORD BP and SPRINT. Issue 18 (18th September 2018) - Beddhu, Srinivasan; Chertow, Glenn M.; Greene, Tom; Whelton, Paul K.; Ambrosius, Walter T.; Cheung, Alfred K.; Cutler, Jeffrey; Fine, Lawrence; Boucher, Robert; Wei, Guo; Zhang, Chong; Kramer, Holly; et al.
Abstract : Background: Intensive systolic blood pressure (SBP) lowering significantly reduced cardiovascular disease (CVD) events in SPRINT (Systolic Blood Pressure Intervention Trial) but not in ACCORD BP (Action to Control Cardiovascular Risk in Diabetes Blood Pressure). Methods and Results: SPRINT tested the effects of intensive (<120 mm Hg) versus standard (<140 mm Hg) SBP goals on CVD events and all‐cause mortality. Using 2×2 factorial design, ACCORD BP tested the same SBP intervention in addition to an intensive versus standard glycemia intervention. We compared the effects of intensive SBP lowering on the composite CVD end point and all‐cause mortality in SPRINT with its effects within each of the glycemia arms in ACCORD BP. Intensive SBP lowering decreased the hazard of the composite CVD end point similarly in SPRINT (hazard ratio: 0.75; 95% confidence interval, 0.64–0.89) and in the ACCORD BP standard glycemia arm (hazard ratio: 0.77; 95% confidence interval, 0.63–0.95; interaction P =0.87). However, the effect of intensive SBP lowering on the composite CVD end point in the ACCORD BP intensive glycemia arm (hazard ratio: 1.04; 95% confidence interval, 0.83–1.29) was significantly different from SPRINT (interaction P =0.023). Patterns were similar for all‐cause mortality. Conclusions: The effects of intensive SBP control on CVD events and all‐cause mortality were similar in patients without diabetes mellitus and in those with diabetes mellitus on standard glycemic control. An interaction between intensive SBP lowering and intensive glycemic control may have masked beneficial effects of intensive SBP lowering in ACCORD BP. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifiers: NCT01206062, NCT00000620.